2017
DOI: 10.1016/j.jdiacomp.2016.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year hemoglobin A1c trajectories and outcomes in type 2 diabetes mellitus: The Diabetes & Aging Study

Abstract: AIMS To classify trajectories of long term HbA1c values in patients after diagnosis of Type 2 diabetes and examine each trajectory's associations with subsequent microvascular and macrovascular events and mortality. METHODS Longitudinal follow-up of 28,016 patients newly diagnosed with Type 2 diabetes. Latent growth mixture modeling to identify ten-year HbA1c trajectories. Cox proportional hazards models to assess how HbA1c trajectories were associated with events (microvascular and macrovascular) and mortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
103
2
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(121 citation statements)
references
References 32 publications
12
103
2
4
Order By: Relevance
“…To our knowledge, only two previous studies have examined latent glycaemic trajectories in patients with type 2 diabetes . Both studies identified four glycaemic trajectories, which had notable similarities to the trajectory patterns we observed in the present study.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…To our knowledge, only two previous studies have examined latent glycaemic trajectories in patients with type 2 diabetes . Both studies identified four glycaemic trajectories, which had notable similarities to the trajectory patterns we observed in the present study.…”
Section: Discussionsupporting
confidence: 83%
“…When compared with white populations, other races tend to have higher HbA1c values, and their inclusion might have resulted in glycaemic control trajectories that differed in size and shape. One of the previous studies that examined latent glycaemic control trajectories included a mixed‐race population, with ~50% non‐white participants; however, as stated before, the identified trajectories in that study were similar to the trajectories in the present study.…”
Section: Discussionsupporting
confidence: 69%
“…Distinct HbA 1c trajectories in recently diagnosed Type 2 diabetes have only been reported in one previous study, based on data from a health maintenance organization in the USA (Kaiser Permanente Northern California), including 28 016 individuals over 10 years after Type 2 diabetes diagnosis . Five HbA 1c trajectories were found: ‘low stable’ (83%); ‘moderate increasing late’ (5%); ‘high decreasing early’ (5%); ‘moderate peaking late’ (4%); and ‘moderate peaking early’ (3%) .…”
Section: Discussionmentioning
confidence: 97%
“…Some studies have shown primary failure rates around 30% [14] and secondary failure rates as high as 42%, with mean failure rates of 12-17% per year [13]. Because of this high failure rate, and because of the positive effects of early treatment and restoration of glycemic control [15], it would be highly beneficial for a clinician to know at the time of treatment initiation whether a specific patient is likely to respond to metformin. If the a priori risk of near-term treatment failure is high, whether it be primary or secondary failure, developing and pursuing an alternative treatment pathway diagnosis may help facilitate effective long-term glycemic control and improve patient outcomes.…”
Section: Background and Significancementioning
confidence: 99%